Does website‐based information add any value in counseling mothers expecting a baby with severe congenital diaphragmatic hernia?. (29th August 2013) - Engels, Alexander C.; DeKoninck, Philip; van der Merwe, Johannes L.; Van Mieghem, Tim; Stevens, Petra; Power, Beverley; Nicolaides, Kypros H.; Gratacos, Eduard; Deprest, Jan A.
ABSTRACT: Objective: We aimed to measure whether website‐provided information about congenital diaphragmatic hernia (CDH) and fetal therapy for severe cases provides added value compared with clinical counseling of parents. Methods: This is a single center study in 102 couples who earlier opted for fetoscopic endoluminal tracheal occlusion (FETO) because of isolated severe CDH. They were asked to fill out an anonymized web‐based survey of 12 questions. Then, they were offered access to information on the web pages of the randomized Tracheal Occlusion to Accelerate Lung Growth (TOTAL) trial. One week later, their appreciation was measured again by a second questionnaire. Results: Eighty‐two (80%) parents completed the first questionnaire, and 48 (47%) completed the entire survey. Several items became more clear to the parents after reading the website, such as the length of hospital stay (23.2% prior to web information, 60.4% after; P  = 0.004), maternal risk, or the requirement of fetal anesthesia for FETO (43.9% resp. 79.2%; P  = <0.001). Conclusion: Complementing prenatal counseling on CDH and FETO by standardized information via website is perceived by parents as of added value. Maternal risks and the need for fetal medication need more clarification during the verbal counseling prior to prenatal interventions. © 2013 John Wiley & Sons, Ltd. Abstract : What's already known about this topic? Parents expecting a baby with CDH should receive as much information as possible about this condition and the treatment options to improve their compliance and therefore the children's outcome. As more and more parents are using the Internet as an information source, we should use the Internet as a complementation in prenatal consultation. What does this study add? This study provides evidence that website‐based information can complement verbal prenatal counseling on fetoscopic procedures as the FETO treatment for CDH. Especially, the maternal risks and the need for fetal medication need to be explained more clearly to the patients during prenatal consultation.